Efforts to Prevent Eye Fatigue Through Evaluation of Lighting Intensity (Illumination Level) in the Library at Muhammadiyah University Lamongan - Uswatun Chasanah; Aris Widodo; Mala Rosa Aprillya (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The Muhammadiyah group has implemented community service programs (PKM) in collaboration with the Universitas Muhammadiyah Lamongan (UMLA) Library. In order to comply with SNI 03-6197-2000 regarding energy conservation in lighting systems, the PKM activity aims to measure and create a contour map of the lighting intensity level (also known as illumination level) in the UMLA library space, increase target partners' knowledge regarding lighting intensity (also known as illumination level) in the work space and its relationship to eye fatigue, and implement technology in the form of an IoT integrated room lighting system. The target partners will be fully involved in all activities, including FGD (First Measurement of Lighting Levels in Library Spaces), counseling regarding lighting intensity (Illumination Level) in work spaces and its relationship to eye fatigue, and the design and implementation of sensor and IoT based room lighting systems. The method for implementing community service activities is a participatory approach. The Muhammadiyah Lamongan University Library Institute, the community service partner, was able to accurately assess the illumination in the interpretation library room by means of a number of completed community service projects. We may conclude that the UMLA library's light intensity, which is ≥ 300 lux, satisfies the SNI criterion.